Maverick politicians : their beliefs and actions : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Policy at Massey University, Albany, New Zealand - Boyd, Hilary Christine (Massey University, 1999)
Through interviews with maverick politicians and political commentators, this research explores the beliefs and actions of maverick politicians, a sub-group of actors within the policy-making process. It builds on previous research which focused primarily on the characteristics and beliefs of maverick politicians. This research was undertaken to ascertain the process by which the politicians attain the maverick label; explore the environment within which these politicians operate; examine the methods maverick politicians use to achieve change in policy, parliamentary practices and the political landscape; and determine their effectiveness in implementing change. Attaining the maverick status involved politicians undergoing a process of alienation from their party. They struggled to implement policy initiatives and adopted an oppositional approach as they battled with an antidemocratic policy-making process. Often unable to effect significant policy changes maverick politicians attempted reformation of the parliamentary practices and the political landscape. However, these attempts merely entrenched existing undemocratic processes. The research findings suggest that because of their underlying beliefs of how Parliament should operate maverick politicians choose to give priority to their constituents rather than to their party and support a notion of democracy that is participatory rather than representative. These choices contribute towards their maverick behaviour; result in alienation from their party; and limit their long-term effectiveness as policy-makers by leading them to focus on reformation. It is likely that, unless changes which accommodate politicians with differing views of representation and democracy occur within the parliamentary and party systems, there will continue to be disillusioned MPs who become alienated from their political parties and follow the maverick path.
Permission has not yet been obtained to make the thesis publicly available.
Keywords: Dissenters; Politicians; New Zealand; Politics and government; 20th century; 440809 New Zealand government and politics